Motivational attribution of students as a basic method in communicative and cognitive approach for the purposes of learning a second foreign language - Belyakova E.A.; Medvedev V.G. (Theory and Practice of Physical Culture, 2024)
Purpose of Research. This research aims at creating the motivational attribution method for students who learn their second foreign language (French) and already have some experience of learning English as their first one. Method and Organization of Research. To create the motivational attribution method we put to analysis relevant literature, run an educational experiment and also applied expert evaluation and mathematical statistics methods (measure of central tendency, like mean value, standard error of the mean as well as the paired comparison method by Wilcoxon, and Spearman’s rank correlation coefficient.) The research was participated by 30 students who study their second foreign language (French) in a sports college and who already have some experience of learning English as their first foreign language. Expert surveys basing on ten motivational attribution factors were done both in the beginning and at the end of the studying period. Results and Conclusions. This research aims at creating a method for motivational attribution of students who learn their second foreign language (French) and already have some experience of learning English as their first one. For this purpose, we put to analysis relevant literature, run an educational experiment and also applied expert evaluation and mathematical statistics methods. The results achieved include definitions of motivational attribution factors as well as model characteristics thereof. The article also describes the method and calculation procedure. The reliability of motivational attribution method has been proved through test-retest.